Shadow ball : new and selected poems - Webb, Charles Harper (Pitt poetry series., 2009)
An accessible new and selected collection of poems for poetry insiders and general readers. Powerful, passionate, humorous, and often complex, yet fun to read. They go down easy, but pack a whallop.